Pengaruh Suku Bunga Bank Indonesia terhadap Nilai Tukar Rupiah terhadap Dolar As (IDR/USD) di Indonesia Periode 2021-2026 - Theresia Imelda Nelly Sianipar; Muhammad Ihsan Noviansyah; Viona Priskila Naftali Manurung; Saniyyah ‘Ulyaa; Namira Farahdiva; Ahmad Setiawan Nuraya (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of the Bank Indonesia interest rate on the Indonesian rupiah exchange rate against the United States dollar during the 2021–2026 period. A quantitative approach was employed using monthly time-series data obtained from official sources. The analysis was conducted using multiple linear regression with the assistance of EViews software. The dependent variable in this study was the rupiah exchange rate against the US dollar, while the independent variables included the Bank Indonesia interest rate, inflation, money supply (M2), and the Federal Reserve interest rate (Fed Rate). Prior to regression estimation, all data were tested for stationarity using the Augmented Dickey-Fuller (ADF) test to ensure compliance with time-series analysis requirements. Furthermore, the model was evaluated through classical assumption tests, including normality, heteroscedasticity, multicollinearity, and autocorrelation tests, to verify the validity and reliability of the estimation results. The findings reveal that the Bank Indonesia interest rate has a significant effect on the rupiah exchange rate, with a probability value of 0.0223. This result indicates that changes in the domestic interest rate can influence movements in the rupiah exchange rate against the US dollar. In contrast, inflation, money supply (M2), and the Fed Rate were found to have no significant effect on the rupiah exchange rate during the study period. Moreover, the classical assumption tests confirmed that the regression model satisfied all required criteria, indicating that the estimated results are reliable and can serve as a reference for economic policy formulation.